Development Strategy for Bali Cattle Farming Based on Forage Availability within a Sustainable Agribusiness Framework - I Putu Gede Didik Widiarta; I Wayan Suarna; Ni Nyoman Suryani; Prihutomo Suharto; I Gede Made Widya Pustaka Jaya (SEAS (Sustainable Environment Agricultural Science), 2026)
Forage availability constitutes a decisive constraint in the development and sustainability of Bali cattle agribusiness within smallholder production systems. This study aims to formulate robust forage-based development strategies for Bali cattle farming under a sustainable agribusiness framework. A mixed-methods design was employed, integrating quantitative assessments of forage biomass production, carrying capacity, cattle productivity, and economic performance with qualitative strategic analysis. Primary data were obtained through structured field observations, in-depth interviews, and focus group discussions involving Bali cattle farmers and key stakeholders in Kecamatan Rendang, Karangasem Regency. Strategic positioning was evaluated using the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) matrix, and SWOT analysis. The results demonstrate that forage availability remains moderate and spatially uneven, directly constraining carrying capacity and production efficiency. The IFE and EFE scores of 2.71 and 2.89 place Bali cattle agribusiness in a selective growth and stability position. SWOT integration confirms that forage-based intensification, crop-livestock integration, and forage conservation practices increase forage availability by 25-32%, improve average daily gain by 18-24%, and reduce feed costs by 15-20%. Sustainability assessment further verifies improvements in nutrient recycling efficiency, soil organic matter, labor productivity, and income stability. These findings conclusively establish forage optimization as a strategic leverage point for strengthening productivity, competitiveness, and sustainability of Bali cattle agribusiness in tropical environments.